Analysis of windlass mechanism according to one walking cycle - Shiroshita, Takashi (Journal of physical therapy science, 2024)
[Purpose] This study aimed to calculate the windlass mechanism in one walking cycle (WC) using the medial longitudinal arch (MLA) height and compare its mechanism with joint moments, angles, and center of gravity movement. [Participants and Methods] The study analyzed the gait of 20 healthy adults (14 males, six females) using a three-dimensional motion analyzer to calculate several parameters. [Results] In the terminal stance, the MLA height reached 20.6 ± 6.0 mm (minimum value) at 49% WC. Simultaneously, the ankle dorsiflexion angle, ankle internal plantarflexion moment, and forward shift of the center of gravity reached the maximum values. At 62% WC, the MLA height was 26.8 ± 4.8 mm and reached maximum during the stance phase, indicating a windlass mechanism. Additionally, the MLA height was 61.7 ± 22.7 mm at 69% WC, indicating an MLA spiking phenomenon. [Conclusion] The MLA height was lowest at 49% WC due to reverse windlass mechanism. Although the windlass mechanism was activated at 62% WC, it was functionally equivalent to the swing phase. Push-off was impossible during the swing phase. At 69% WC, the swing phase showed a second windlass mechanism.